Implications of Virtual Classroom Management: A Review of Challenges and Prospects - Muhammad Muhammad Suleiman; Surajo Musa Yakubu; Safiyanu Sulaiman Saleh; Haruna Ibrahim, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
The COVID-19 pandemic has revolutionised the traditional educational system, requiring schools and universities to implement virtual classrooms as a viable way of continuing operations. This shift has presented several challenges to classroom management, yet it also presents educators with new prospects for engaging their students in the virtual learning space. This review assesses the implications of virtual classroom management, its relevance to current educational practice, and offers strategies for successful implementation. Finally, this review provides a comprehensive overview of the challenges and prospects of virtual classroom management. While the challenges are significant, the potential of virtual classrooms to create meaningful learning experiences is undeniable. It must be harnessed by schools and universities if educational outcomes are to be achieved in the post-pandemic environment.